Learned helplessness the effect of failure on test-taking - Firmin, Michael; Chi-en, Hwang; Copella, Margaret; Clark, Sarah
This study examined learned helplessness and its effect on test taking. students were given one of two tests; the first began with extremely difficult questions and other started with easy questions. We hypothesized that those who took the test beginning with difficult questions would become easily frustrated and possibly doubt their intellectual ability. This would result in the participants missing easy questions when compared to those who took the test which began with easy questions. the result of the study confirmed our hypothesis. the result of this study could also be applied to other classroom tests and standardized tests where learned helplessness could negatively affect test scores.